2017
DOI: 10.3389/fpsyg.2017.00689
|View full text |Cite
|
Sign up to set email alerts
|

A Deficit in Movement-Derived Sentences in German-Speaking Hearing-Impaired Children

Abstract: Children with hearing impairment (HI) show disorders in syntax and morphology. The question is whether and how these disorders are connected to problems in the auditory domain. The aim of this paper is to examine whether moderate to severe hearing loss at a young age affects the ability of German-speaking orally trained children to understand and produce sentences. We focused on sentence structures that are derived by syntactic movement, which have been identified as a sensitive marker for syntactic impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 59 publications
2
10
0
12
Order By: Relevance
“…An increasing number of studies show that hearing impairment has severe consequences on the development of oral language abilities. Individuals with hearing loss have difficulties especially with the acquisition of complex sentences, such as relative clauses, topicalized sentences and wh- questions across different languages (English: De Villiers et al, 1994; French: Tuller & Delage, 2014; German: Penke & Wimmer, 2018; Ruigendijk & Friedmann, 2017; Italian: Volpato, 2010, 2012; Volpato & Adani, 2009; Volpato & Vernice, 2014; Hebrew: Friedmann & Szterman, 2006, 2011; Palestinian-Arabic: Friedmann & Haddad-Hanna, 2014). These studies observed that sentences involving the movement of the object DP to the sentence-initial position are more difficult to comprehend, produce and repeat than those containing subject movement.…”
Section: Grammatical Deficits In Dhh Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies show that hearing impairment has severe consequences on the development of oral language abilities. Individuals with hearing loss have difficulties especially with the acquisition of complex sentences, such as relative clauses, topicalized sentences and wh- questions across different languages (English: De Villiers et al, 1994; French: Tuller & Delage, 2014; German: Penke & Wimmer, 2018; Ruigendijk & Friedmann, 2017; Italian: Volpato, 2010, 2012; Volpato & Adani, 2009; Volpato & Vernice, 2014; Hebrew: Friedmann & Szterman, 2006, 2011; Palestinian-Arabic: Friedmann & Haddad-Hanna, 2014). These studies observed that sentences involving the movement of the object DP to the sentence-initial position are more difficult to comprehend, produce and repeat than those containing subject movement.…”
Section: Grammatical Deficits In Dhh Childrenmentioning
confidence: 99%
“…Movement of the object to a non-canonical position involves a marked word order of constituents, in which the theme precedes the agent. In German RCs, agent and theme are also marked for case, but this cue does not help DHH children in theta-role assignment (Ruigendijk & Friedmann, 2017). The difficulties might be due to the computational complexity involved in the derivation of these sentences (Tuller & Delage, 2014) in order to process, for instance, the movement of a full NP (the object) across another NP (the subject) (Friedmann et al, 2009).…”
Section: Grammatical Deficits In Dhh Childrenmentioning
confidence: 99%
“…Many studies reported that orally-trained DHH children have difficulties in the comprehension and production of structure derived by syntactic movement, such as object relative clauses, object Wh-questions, and topicalized structures [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. These structures are derived by movement of the object noun phrase across a subject noun phrase.…”
Section: Discussionmentioning
confidence: 99%
“…In Hebrew, movement of the verb to the second position in the sentence, before the subject, is optional, so that both “Yesterday ate the girl hummus” and “Yesterday the girl ate hummus” are acceptable [ 49 , 50 , 51 ]. Difficulties of DHH in such verb movement structures were reported for Hebrew [ 52 , 53 , 54 ] and German [ 43 ].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation